Stability of nonlinear variable-time impulsive differential systems with delayed impulses. (February 2021) - He, Zhilong; Li, Chuandong; Cao, Zhengran; Li, Hongfei
Abstract: This paper investigates the stability of nonlinear variable-time impulsive differential systems with delayed impulses. By using the comparison principle, the Lyapunov method and inequality techniques, some sufficient conditions for quasi-uniformly asymptotic stability and quasi-exponential stability of a given solution of variable-time impulsive differential systems with delayed impulses are established.